Perfil hematológico de cabras Saanen e mestiças (1/2 Saanen e 1/2 Anglo-nubiana) criadas em clima tropical do Ceará - Souza, Priscila T.; Salles, Maria Gorete F.; Costa, Antonio Nelson L.; Carneiro, Hilton A. V.; Souza, Leonardo P. [UNESP]; Rocha, David R.; Araujo, Airton A. (Revista Pesquisa Veterinaria Brasileira, 2015)
The aim of this study was to determine the influence of climatic conditions on the hematological profile of Saanen and mixed-breed (1/2 Saanen x 1/2 Anglo-Nubian) goats, as well as to define reference values for these animals bred in Ceara, Brazil. Thirty goats were utilized and blood samples were collected monthly during the rainy (February to May) and dry (August to November) periods to obtain an erythrogram a leukogram. The averange were compared by the t-Student test and Mann Whitney test, with parametric and non-parametric distribution of the data, respectively, where p<0.05 was considered significant. A study was carried out of simple Pearson correlations of the hematological parameters with environmental and physiological variables. The number of red blood cells (RBCs) was higher in the Saanen goats and in the rainy period, while the hematocrit was higher in the dry period (p<0.05). The leukocytes and lymphocytes were higher in the 1/2S1/2 AN goats in the two periods (p<0.05). In the two genotypes, the leukocytes and lymphocytes were higher in the dry season and the segmented neutrophils higher in the rainy season (p<0.05). The other parameters did not differ (p>0.05). The RBCs and segmented neutrophils displayed a negative correlation with air temperature, but positive with relative humidity and rectal temperature (p<0.05). The hematocrit positively correlated with air temperature and respiratory rate (p<0.05). The leukocytes and lymphocytes showed a negative correlation with rectal temperature (p<0.05). It was therefore concluded that Saanen females are more affected by climatic variations and that the rainy season has a greater negative impact on hematological parameters. The values obtained could serve as a reference for these genotypes in Ceara.

Objetivou-se verificar a influência das condições climáticas sobre o perfil hematológico de cabras Saanen e mestiça (1/2 Saanen x 1/2 Anglo-nubiana), bem como determinar valores de referência para esses animais criados no Ceará. Foram utilizadas 30 cabras que tiveram o sangue coletado mensalmente durante a época chuvosa (fevereiro a maio) e seca (agosto a novembro) para realização do eritrograma e leucograma. As médias foram comparadas pelo teste t-Student e Mann Whitney, quando constatada distribuição paramétrica e não paramétrica dos dados, respectivamente, com significância quando p<0,05. Procedeu-se ainda um estudo de correlações simples de Pearson dos parâmetros hematológicos com variáveis ambientais e fisiológicas. O número de hemácias foi maior em cabras Saanen e na época chuvosa, enquanto que o hematócrito foi maior na época seca (p<0,05). Os leucócitos e linfócitos foram maiores em cabras mestiças nas duas épocas (p<0,05). Nos dois genótipos, os leucócitos e linfócitos foram maiores na época seca e os neutrófilos segmentados maiores na época chuvosa (p<0,05). Os demais parâmetros não diferiram (p>0,05). As hemácias e neutrófilos segmentados apresentaram uma correlação negativa com a temperatura ambiente, porém positiva com a umidade do ar e a temperatura retal (p<0,05). O hematócrito correlacionou-se positivamente com a temperatura ambiente e frequência respiratória (p<0,05). Os leucócitos e linfócitos mostraram uma correlação negativa com a temperatura retal (p<0,05). Conclui-se, portanto, que fêmeas Saanen sofrem mais influência das variações climáticas e a época chuvosa tem maior impacto negativo sobre os parâmetros hematológicos. Os valores obtidos poderão servir como referência para esses genótipos no Ceará.
Hematological profile of Saanen and mixed-breed (1/2 Saanen x 1/2 Anglo-Nubian) raised in the tropical climate of Ceara, Brazil
Keywords: Hematological profile; goats; Saanen; Erythrocyte; Leukocyte; Tropical climate; Perfil hematológico; Caprinos; Saanen; Eritrograma; Leucograma; Clima tropical